2022
DOI: 10.3390/machines10090786
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Measurement and Numerical Modeling Analysis of Transformer Windings and Iron Cores Based on Voltage and Current Harmonics

Abstract: The operating condition and structural state of the converter transformer are closely related to vibration. Abundant harmonics aggravate the vibration of windings and iron cores, resulting in frequent mechanical structural failures, which seriously affect the stable operation of the power system. Traditional research mainly focuses on the vibration of AC transformers without harmonics and there is no in-depth discussion of the vibration mechanism and the numerical calculation model of windings and iron cores u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…According to the existing research, the noise frequency band of an oil-immersed power transformer is distributed in the range of 20-1000 Hz [41]. The most crucial frequency is centred around 100 Hz [42]; for this reason, in our study of the characteristics of bubbles under coupled vibration and electric stresses, 25, 50, and 100 Hz were selected. According to ZTZ Service, a normally operating transformer has the following vibration parameters: vibration speed should be lower than 10 mm/s, acceleration less than 10 m/s 2 , and vibration displacement of 100 µm.…”
Section: Influence Of Coupling Stress On Bubble Deformation and Migra...mentioning
confidence: 99%
“…According to the existing research, the noise frequency band of an oil-immersed power transformer is distributed in the range of 20-1000 Hz [41]. The most crucial frequency is centred around 100 Hz [42]; for this reason, in our study of the characteristics of bubbles under coupled vibration and electric stresses, 25, 50, and 100 Hz were selected. According to ZTZ Service, a normally operating transformer has the following vibration parameters: vibration speed should be lower than 10 mm/s, acceleration less than 10 m/s 2 , and vibration displacement of 100 µm.…”
Section: Influence Of Coupling Stress On Bubble Deformation and Migra...mentioning
confidence: 99%
“…However, the influence of the edge effect was not considered. Based on the research status at home and abroad [6,[14][15][16][17][18][19], at this stage, scholars in various countries have focused on the study of electromagnetic vibration in rotating motors, and there are relatively few studies on the vibration and noise of linear motors and the LPST. One of the important research points is the influence of the end effect on the air gap electromagnetic force.…”
Section: Introductionmentioning
confidence: 99%
“…However, the above study ignored the fact that during the actual operation of the transformer, the existence of the closed magnetic circuit of the core, the electrical circuit of the windings and the gate ring, and thus, the formation of the closed circuit, resulting in additional electromagnetic force on some structural parts; this produces nonlinear characteristics of the closed magnetic circuit, the electrical circuit and the gate ring, and thus introduces additional harmonic and nonharmonic components, resulting in the accuracy of the vibration-signal-based fault diagnosis. In [22][23][24], by studying the force characteristics and vibration characteristics of the transformer core and windings in a harmonic environment, it was found that the vibration energy distribution was shifted from the low-frequency band to the high-frequency band after the harmonics were injected, but the existing studies did not make use of this feature in the transformer fault diagnosis research.…”
Section: Introductionmentioning
confidence: 99%